SAT0256 Juvenile Systemic Sclerosis Cohort within The Childhood Arthritis and Rheumatology Research Alliance (CARRA) Legacy Registry: Baseline and Follow Up Characteristics. (15th July 2016) - Stevens, B.; Torok, K.S.; Li, S.; Hershey, N.; Curran, M.; Higgins, G.; Moore, K.; Rabinovich, E.; Stevens, A.M.; ,
Abstract : Background: Systemic sclerosis (SSc) is a rare multisystem autoimmune disease characterized by vasculopathy and organ fibrosis. From 2010–2013, the North American CARRA Legacy Registry enrolled and prospectively followed children with rheumatologic conditions including juvenile systemic sclerosis (jSSc). Objectives: Describe disease manifestations, physician metrics, and patient quality of life (QOL) at enrollment and follow up of jSSc subjects. Methods: Descriptive statistics were used for demographic and clinical features. We used McNemar's test for paired data and Fisher's exact for group comparisons. Results: For the 64 children with SSc in the database, the majority were female (84%) and Caucasian (78%); 86% identified as non-Hispanic. Median age of onset was 10.3 yr while age at first pediatric rheumatology (PRH) evaluation was 11.8 yr, with 23% having a ≥2 yr delay to PRH. Baseline visit occurred a median of 3.6 yrs after disease onset and data obtained 1–2 yr from enrollment was analyzed for follow up (n=25, median 1.4 yrs). For those with complete clinical data, 81% met ACR/EULAR 2013 adult criteria for SSc at baseline. Overlap with juvenile dermatomyositis was reported in 3 individuals, with mixed connective tissue disease in 1. Of those with documented testing for specific antibodies, 80% were ANA positive, 46% anti-Scl70 and 15% ACA. Three of 15 patients tested for anti-PM-Scl antibodies were positive. At baseline, the most prevalent organ manifestations were dermatologic (93%) and vascular (92%), with Raynaud phenomenon as the most common feature. Multiple organs were affected in 93%, and 38% had ≥4 organ systems involved. Disease manifestations remained stable at follow up with the exception of decreased frequency of arthritis (4 to 1) and increased joint contractures (7 to 11). At conclusion of the study, no interval development of renal, cardiac, or pulmonary manifestations or mortalities occurred. Frequency of disability, measured by ACR functional class, decreased from 44% at baseline to 25% at follow up. Median Physician Global Disease Activity scores improved from 3 (IQR 1–4) to 2 (1–3), with trending significance for those with <2 years of disease at enrollment (n=7, p= 0.059). While there were no statistically significant differences in QOL measures over time, trends of improvement in pain scale (3.5 to 2) and global well-being scale (5 to 3) were appreciated in this early disease group. Conclusions: Even with inclusion of overlap patients, baseline clinical data from this cohort are similar to the jSSc cohort described by Martini et al in 2006 and most met current ACR/EULAR adult SSc criteria. Most organ manifestations were stable with time and for the duration of the study observation period, there was no interval development of major organ involvement or mortality. While limited by the cross sectional nature of enrollment, trends of improvement in disability and disease activity were appreciated after 1–2 years of follow up. References: Martini G, et al. Systemic Sclerosis in Childhood. Arthritis Rheum 2006;54:3971–8 van den Hoogen F, et al. 2013 classification criteria for systemic sclerosis. Arthritis Rheum 2013;65:2737–47 Disclosure of Interest: B. Stevens: None declared, K. Torok: None declared, S. Li: None declared, N. Hershey: None declared, M. Curran: None declared, G. Higgins: None declared, K. Moore: None declared, E. Rabinovich Grant/research support from: Abbie Vie; UCB Pharma; Hoffmann-La Roche Inc.; Janssen Research & Development, LLC, A. Stevens: None declared